Effects of the Absorption Behaviour of ZnO Nanoparticles on Cytotoxicity Measurements. (25th February 2014) - Najim, Nigar; Rusdi, Roshidah; Hamzah, Ahmad Sazali; Shaameri, Zurina; Mat Zain, Mazatulikhma; Kamarulzaman, Norlida
Abstract : ZnO absorbs certain wavelengths of light and this behavior is more pronounced for nanoparticles of ZnO. As many toxicity measurements rely on measuring light transmission in cell lines, it is essential to determine how far this light absorption influences experimental toxicity measurements. The main objective was to study the ZnO absorption and how this influenced the cytotoxicity measurements. The cytotoxicity of differently sized ZnO nanoparticles in normal and cancer cell lines derived from lung tissue (Hs888Lu), neuron-phenotypic cells (SH-SY5Y), neuroblastoma (SH-SY5Y), human histiocytic lymphoma (U937), and lung cancer (A549) was investigated. Our results demonstrate that the presence of ZnO affected the cytotoxicity measurements due to the absorption characteristic of ZnO nanoparticles. The data revealed that the ZnO nanoparticles with an average particle size of around 85.7 nm and 190 nm showed cytotoxicity towards U937, SH-SY5Y, differentiated SH-SY5Y, and Hs888Lu cell lines. No effect on the A549 cells was observed. It was also found that the cytotoxicity of ZnO was particle size, concentration, and time dependent. These studies are the first to quantify the influence of ZnO nanoparticles on cytotoxicity assays. Corrections for absorption effects were carried out which gave an accurate estimation of the concentrations that produce the cytotoxic effects.